Survey of the effect of doxorubicin and flavonoid extract of white Morus alba leaf on apoptosis induction in a-172 GBM cell line. (15th March 2019) - Dabili, Sheyda; Fallah, Soudabeh; Aein, Mojdeh; Vatannejad, Akram; Panahi, Ghodratollah; Fadaei, Reza; Moradi, Nariman; Shojaii, Asie
Abstract: In this study, the effect of doxorubicin, flavonoid extract of white Morus alba leaf (MFE) and a combination of doxorubicin and flavonoid extract on Bax and Bcl2 levels and caspase 3 activity of cancer A-172 GBM cell line was investigated. Bax/Bcl2 levels of treated A-172 GBM cell line with flavonoid extract of white mulberry leaf were estimated by ELISA methods. Caspase 3 activity of treated A-172 GBM cells was determined by calorimetric assay. The flow cytometry assessment was used to estimate the apoptosis percent of treated A-172 GBM cells. Treatment of A-172 GBM cells with MFE, doxorubicin and a combination of MFE and doxorubicin caused a significant decrease in Bcl2 level and an increase in Bax level. The apoptosis percent of treated cells were also elevated significantly. Present results suggest that concomitant use of herbal medicine and chemotherapy may be an effective alternative method for the treatment of cancers.